The Coevolution of Network Alliances: A Longitudinal Analysis of an International Professional Service Network - Koza, Mitchell P.; Lewin, Arie Y. (Organization Science, 1999)
This paper examines a single longitudinal case study of a professional service network in the public accounting industry, a network intentionally created and formally organized to pursue residual referral revenue for the member firms. Applying and extending a coevolutionary perspective (Koza and Lewin 1998), the paper explores the antecedents and stimuli for the formation of the network, the network's morphology, the motivation of the network members, and the ways in which the network coevolves with its environment and with the adaptation practices of its members. We find that the network was initially created with the strategic intent of producing incremental income in exchange for cross-border referrals. However, we also find that this strategy reveals asymmetric positive returns, which produce serendipitous opportunities for individual member firms to bypass the original intent of network by entering each other's market. We propose that such tensions may be endemic to alliance networks, and we explore their sources and consequences on a variety of characteristics, including network stability, member opportunism, and control. The paper concludes with a model of the coevolutionary process.